2008
DOI: 10.1161/strokeaha.107.512756
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Clinical Outcome of Patients Harboring Unruptured Intracranial Aneurysms Treated by Endovascular Approach

Abstract: MD; for the ATENA InvestigatorsBackground and Purpose-The management of unruptured intracranial aneurysms remains controversial and the results of endovascular treatment are not precisely known because no prospective data exist. The first prospective multicenter study (ATENA) was conducted in Canada and France to determine clinical outcome and risks of this treatment. Methods-Six hundred forty-nine patients harboring a total of 1100 aneurysms from 27 Canadian and French neurointerventional centers were prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
215
6
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(254 citation statements)
references
References 25 publications
20
215
6
13
Order By: Relevance
“…4,6 In this series, adequate occlusion was obtained in the whole population (narrow and wide-neck aneurysms) and in 80.4% at midterm follow-up after bare platinum coil treatment. In wide-neck aneurysms, the rate of adequate occlusion was 68.2%, which is much lower than the 89% observed in the present series.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…4,6 In this series, adequate occlusion was obtained in the whole population (narrow and wide-neck aneurysms) and in 80.4% at midterm follow-up after bare platinum coil treatment. In wide-neck aneurysms, the rate of adequate occlusion was 68.2%, which is much lower than the 89% observed in the present series.…”
mentioning
confidence: 58%
“…Moreover, no retreatment was performed in the present series, and that is a major advantage compared with what was reported in CLARITY (6.2%) and in the Ferns et al review (10.3%). [4][5][6] These anatomic results are very satisfying because of our selected population that included mostly wide-neck and fusiform intracranial aneurysms. Stent tolerance is another major concern with flow-diverter stents.…”
mentioning
confidence: 76%
“…Two recent multicenter studies have demonstrated that adjunctive techniques were necessary in approximately 45% of cases. 13,14 Thus, our practice with adjunctive techniques does not seem to be unusual.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] However the choice between surgical and endovascular approaches for the treatment of aneurysms in this location is still a matter of debate. 4 Furthermore, wide-neck MCA bifurcation lesions can sometimes prove challenging for traditional EVT approaches, and numerous techniques have been developed to address these cases.…”
mentioning
confidence: 99%